2011
DOI: 10.1007/s10526-011-9407-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hybrid vigor between flightless lines to restore survival and reproductive characteristics in the ladybird beetle Harmonia axyridis

Abstract: The effectiveness of hybrid vigor, which can counteract deleterious effects of inbreeding in flightless Harmonia axyridis Pallas (Coleoptera: Coccinellidae), was investigated. First, we performed the reciprocal cross between two isofemale lines and compared survival and reproductive characteristics between isofemale and hybrid lines under laboratory conditions. The survival of one of the hybrid lines was significantly higher than that of the two isofemale lines. Early fecundity tended to be higher in the two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Our study revealed a high level of heterogeneity in the invasive population. High genetic diversity is commonly considered an important prerequisite for a biological invasion by the multicoloured Asian ladybird (Facon et al, 2008Lombaert et al, 2010;Turgeon et al, 2011;Seko et al, 2012). Moreover, meta-analysis of the data on various invaders suggests that high levels of genotypic diversity in founder groups increase establishment success (Forsman, 2014), although there are exceptions to this rule (Handley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed a high level of heterogeneity in the invasive population. High genetic diversity is commonly considered an important prerequisite for a biological invasion by the multicoloured Asian ladybird (Facon et al, 2008Lombaert et al, 2010;Turgeon et al, 2011;Seko et al, 2012). Moreover, meta-analysis of the data on various invaders suggests that high levels of genotypic diversity in founder groups increase establishment success (Forsman, 2014), although there are exceptions to this rule (Handley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are not only of theoretical but also of practical importance. Several authors note that hybridization between individuals from different native, invasive and mass-reared populations of H. axyridis has had an effect on the worldwide spread of this species (Facon et al, 2008Lombaert et al, 2010;Handley et al, 2011;Turgeon et al, 2011;Seko et al, 2012). Thus, the mode of inheritance of diapause regulation could be a signifi cant factor in the further spread of the multicoulored Asian ladybird.…”
Section: Introductionmentioning
confidence: 99%
“…inbreeding) in a population of insects over many generations can have detrimental effects on the health of a colony and on the performance of individuals released in the field (Mackauer, 1976;Roush and Hopper, 1995). Inbreeding may reduce the fitness of coccinellids such as A. bipunctata, C. maculata, H. axyridis, and Propylea quatuordecimpunctata (L.) (Kidd, 1993;Hurst et al, 1996;Morjan et al, 1999;Facon et al, 2011;Seko et al, 2012). Methods to reduce or prevent the deterioration of colonies may include manipulative breeding between hybrids to restore normal growth, survival, and reproductive capacities of populations in culture.…”
Section: Preventing Colony Deteriorationmentioning
confidence: 99%
“…Hippodamia convergens within the designated Western and Eastern populations in the United States have likely adapted to varying natural conditions, pathogens and parasitoids cycles. Augmenting populations by bringing Western and Eastern populations together to create hybrids can also potentially increase the fitness of the hybrid population, a phenomenon that is commonly described as ‘hybrid vigor’ (Seko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%